Serine and Alanine as Corrosion Inhibitors for 5083 AA in Aqueous Solutions - Zainab W. Ahmed (Journal of Global Pharma Technology, 2016)
By means of potentiodynamic polarization methods, inhibiting the influence of serine and alanine on 5083 AA corrosion in 0.1 mol.dm-3 sodium hydroxide and 140.6 mol. dm-3 NaCl